Trace elements and morphological studies using ICP–OES and SEM investigations - Chandra Prasad Khatiwada (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
The present study has attempt to analyze the changes in the biochemical and mineral contents of aluminum intoxicated bone and determine the protective action of desferrioxamine (DFO) and deferiprone (DFP) by using inductively coupled plasma optical emission spectroscopy (ICP–OES), and scanning electron microscopy (SEM) techniques. The present results suggest that DFO and DFP are the carbonate inhibitor, recovered from chronic growth of bone diseases and pathologies. The concentrations of trace elements were found by ICP–OES. Therefore, present study suggests that due to aluminum toxicity severe loss of bone minerals, decrease in the biochemical constituents and changes in the surface morphology.